2006
DOI: 10.1002/cbf.1228
|View full text |Cite
|
Sign up to set email alerts
|

Liver parenchyma heterogeneity in the response to extracellular NAD+

Abstract: The perfused rat liver responds intensely to NAD+ infusion (20-100 microM). Increases in portal perfusion pressure and glycogenolysis and transient inhibition of oxygen consumption are some of the effects that were observed. The aim of the present work was to investigate the distribution of the response to extracellular NAD+ along the hepatic acinus. The bivascularly perfused rat liver was used. Various combinations of perfusion directions (antegrade and retrograde) and infusion routes (portal vein, hepatic ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Oxygen gradient 53,54 CCC Cell size 41 15-20 mm 30-40 mm Kupffer cells 39,40 Phagocytosis Cytotoxicity Endothelial cells -Fenestrae 39,40 Larger Smaller Stellate cells and Pit cells 39,40 CCC Sympathetic nerves 50 CCC Glucagon receptors 75 CCC Insulin receptors 52 CCC Insulin/glucagon levels 76 CCC Mitochondria and aerobic metabolism 36 CCC Glucose uptake and glycolysis 50 CCC Glucose release: gluconeogenesis 36 CCC Glucose release: glycogenolysis 56 CCC ß-oxidation and ketogenesis 50 CCC Peroxisomal lipid oxidation 70 CCC Triglycerides 59 and VLDL synthesis 83 CCC Cholesterol and bile synthesis 71 CCC Glycogen synthesis from glucose 59 CCC Glycogen synthesis from pyruvate and lactate 50 CCC Uptake of the majority of amino acids 70 CCC CCC Uptake of glutamate and aspartate 70 Uptake of a-ketoglutarate and malate 70 CCC CCC Glutamine synthesis and release 60 Amino acid catabolism and urea synthesis 59 CCC Uric acid synthesis from adenosine 57 CCC Glutation peroxidase and ROS detoxification 50 CCC Table 1B. Zonation of enzyme activity and protein synthesis in liver.…”
Section: Periportal Zone Perivenous Zonementioning
confidence: 98%
“…Oxygen gradient 53,54 CCC Cell size 41 15-20 mm 30-40 mm Kupffer cells 39,40 Phagocytosis Cytotoxicity Endothelial cells -Fenestrae 39,40 Larger Smaller Stellate cells and Pit cells 39,40 CCC Sympathetic nerves 50 CCC Glucagon receptors 75 CCC Insulin receptors 52 CCC Insulin/glucagon levels 76 CCC Mitochondria and aerobic metabolism 36 CCC Glucose uptake and glycolysis 50 CCC Glucose release: gluconeogenesis 36 CCC Glucose release: glycogenolysis 56 CCC ß-oxidation and ketogenesis 50 CCC Peroxisomal lipid oxidation 70 CCC Triglycerides 59 and VLDL synthesis 83 CCC Cholesterol and bile synthesis 71 CCC Glycogen synthesis from glucose 59 CCC Glycogen synthesis from pyruvate and lactate 50 CCC Uptake of the majority of amino acids 70 CCC CCC Uptake of glutamate and aspartate 70 Uptake of a-ketoglutarate and malate 70 CCC CCC Glutamine synthesis and release 60 Amino acid catabolism and urea synthesis 59 CCC Uric acid synthesis from adenosine 57 CCC Glutation peroxidase and ROS detoxification 50 CCC Table 1B. Zonation of enzyme activity and protein synthesis in liver.…”
Section: Periportal Zone Perivenous Zonementioning
confidence: 98%
“…Extracellular NAD + at micromolar levels can regulate intracellular calcium levels and also induces superoxide and nitric oxide generation and enhances chemotaxis in granulocytes [69]. Oxygen uptake is stimulated by extracellular NAD + in rat liver [70]. The P2 receptor (P2X7) is involved in the action of NAD + and ATP on regulatory T cells [71].…”
Section: Hypothesis For the Roles Of Ganglio-sides On Regulation Of Ementioning
confidence: 99%
“…[15][16][17][18] The main advantage in comparison with diabetic rats is that normal rats maintain the integrity of the hormonal counter regulatory system and it is possible to study the participation of the liver to prevent the hypoglycemia without the interference caused by the chronic hyperglycemia of diabetic states. 19 By using these fed rats, a favorable condition to study glycogenolysis, 20 we demonstrated that hepatic glycogen concentration, and the basal activities of glycogen phosphorylase and glycogen synthase were not modified during shortterm IIH. 6,7 Thus, the well-established short-term IIH in fed rats 6,7 could be attributable to the fact that the release of endogenous glucagon and epinephrine could not overcome the inhibitory effect of the insulin injection on glycogen phosphorylase activity and the stimulatory effect of insulin on glycogen synthase activity.…”
Section: Discussionmentioning
confidence: 97%